Effect of 4-phenylbutyrate addition timing on titer of Fc-fusion protein in Chinese hamster ovary cell cultures - Lim, Jungae; Lim, Jin-Hyuk; Lee, Ji-Hoon; Cheon, Su-Hwan; Lee, Guewha; Kim, Z-Hun; Kim, Dong-Il (Biotechnology and bioprocess engineering, 2024)
Chinese hamster ovary (CHO) cells have been widely used in the biotechnology industry for the production of therapeutic proteins, leading to various research efforts to increase the productivity of therapeutic proteins. Although the addition of small molecule enhancers in CHO cell culture can enhance productivity, it poses a problem by negatively affecting product quality. In this study, effects of 4-phenylbutyrate (4-PBA), a chemical chaperone having a positive influence on recombinant protein production in CHO cells, were investigated. By varying the timing of 4-PBA addition, it was confirmed that the titer could be increased by 1.57-fold while reducing negative effects such as growth inhibition and apoptosis, thus preserving product quality. These effects of 4-PBA demonstrate the potential of using additive for developing novel enhancers for the production of recombinant proteins and the development of strategies for CHO cell engineering.